Sell-Side Information Production in Financial Markets - Chen, Zhaohui; Wilhelm, William J. (Journal of Financial and Quantitative Analysis, 2012)
Abstract We study decisions to sell nonexcludable private information in the presence of a trading opportunity. Sell-side agents heighten competition among agents who buy their signals to combine with their own for proprietary trading purposes and thereby promote financial market efficiency. This result holds even when the sell-side production technology is not unique. But sell-side information is subject to underinvestment if producers do not internalize the benefits. The model suggests that fee-based compensation for corporate advisory services diminishes this problem and that market efficiency is undermined by forces steering investment-banking resources toward proprietary trading.